2021
DOI: 10.1007/s42452-021-04201-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of the SWAT model for estimating reservoir volume in the Upper Navet watershed in Trinidad

Abstract: In tropical small islands the application of hydrological modelling is challenged by the scarcity of input data. Using in-situ and statistically estimated data, a hydrological model was calibrated and validated for the Upper Navet watershed in Trinidad, a small Caribbean island. The model was built using the soil water assessment tool (SWAT). The sensitivity analysis, calibration and validation were performed in SWAT calibration and uncertainty program (SWAT-CUP) using sequential uncertainty fitting (SUFI-2). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…They pointed out that CN2, SOL_AWC, HRU_SLP, GW_DELAY, and CNCOEFF are the most sensitive parameters in the combined simulation analysis of streamflow and sediment yield. A reservoir modeling study by Beharry et al (2021) found 16 sensitive parameters (ALPHA_BNK, CH_K2, GW_DELAY, ALPHA_BF, CH_N2, CN2, EPCO, OV_N, REVAPMN, SURLAG, SOL_K, SOL_BD, GWQMN, SOL_AWC, and GW_REVA) in their study. Almost the same parameters were deemed sensitive in this study.…”
Section: Discussionmentioning
confidence: 97%
“…They pointed out that CN2, SOL_AWC, HRU_SLP, GW_DELAY, and CNCOEFF are the most sensitive parameters in the combined simulation analysis of streamflow and sediment yield. A reservoir modeling study by Beharry et al (2021) found 16 sensitive parameters (ALPHA_BNK, CH_K2, GW_DELAY, ALPHA_BF, CH_N2, CN2, EPCO, OV_N, REVAPMN, SURLAG, SOL_K, SOL_BD, GWQMN, SOL_AWC, and GW_REVA) in their study. Almost the same parameters were deemed sensitive in this study.…”
Section: Discussionmentioning
confidence: 97%
“…In the calibration and validation of the model, the SUFI2 method was used and parameters within the hydrologic response unit, groundwater, streamflow, and soils were modified. Details and supporting evidence for the model performance statistics to estimate the volume of water in the Upper Navet Reservoir can be found in Beharry et al (2021). Figure 2 illustrates the flow chart for the calibration/validation of the model together with the main steps in the estimation of the future reservoir volume, under each RCP, for the short, medium, and long terms.…”
Section: Estimation Of Future Reservoir Volumesmentioning
confidence: 99%
“…The inherited uncertainty of the calibrated and validated Navet hydrological model suggested that 71% of the observed data should be enveloped with the 95PPU (Beharry et al, 2021). It is acknowledged that additional sources of uncertainties may also have been added from the future climate conditions and concentration pathways, data assumptions, errors in the GCM predictors, errors in downscaling the precipitation, and errors in the SWAT model (Pervez & Henebry, 2015).…”
Section: Years (Total)mentioning
confidence: 99%
“…volumes (Beharry et al 2021), and explain rainfall-runoff relationships (Liu and Todini 2002) and assess hydrological impacts of global circulation patterns (Liang et al 1994), and determine occurrence of floods (Borah 2011;Costabile et al 2013;Costabile and Macchione 2015). The processing of hydrological parameters for the development of physically based models requires expertise, high-quality data, and detailed knowledge of the basin processes (Kim et al 2015a).…”
Section: Highlightsmentioning
confidence: 99%